FLAVONOID GLYCOSIDES FROM THE LEAVES OF CISSUS IBUENSIS HOOK (VITACEAE) - Ahmadu, A. A.; Onanuga, A.; Aquino, R. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
The bioactive N-butanol fraction of the ethanol extract of the leaves of Cissus ibuensis was fractionated over silica Gel column to give Quercetin 3-O-rutinoside (I) and mixtures of Flavonoids (A2). A2 was fractionated using reverse phase HPLC to give Kaempferol 3-O-α-rhamnopyranosyl (1→6)-β-D-galactopyranoside (II), Kaempferol 3-O-rutinoside(III)and Kaempferol3-O-α-rhamnopyranosyl(1→6)-α-rhamnopyranosyl(1→2)-β-D-galactopyranoside (IV). The structures were elucidated by NMR spectroscopy and compared with literature.